Interview of Martin A. Pomerantz by Brian Shoemaker - Pomerantz, Martin A., 1916- (Byrd Polar Research Center Archival Program, 2006)
Baird, George, physicist, pp. 42, 45 Bentley, Charlie, geophysicist, pp. 70-71 Fossat, Eric, French astronomer, pp. 51-52 Friedman, Herbert, nuclear physicist, p. 14 Holsrichter, Harry, Navy physician, p. 37 Jackson, Bernie, astronomer, p. 52 Jezek, Ken, Director of the Byrd Polar Institute, pp. 69-70 Jones, Tom, Haverford College, first Director, Office of Polar Programs, p. 21 Merrifield, Bill, theorist in helio-seismology, pp. 70-71 Newberg, Hugo, cosmic ray physicist, p. 24 Ramsey, Norman, nuclear physicist at Harvard, pp. 11-12 Simpson, John, nuclear physicist, University of Chicago, pp. 8, 14, 18 Stark, Tony, astronomer, p. 62 Van Allen, James, nuclear physicist, pp. 9, 13-14, 18 Wilson, Bob, Noble Prize astronomer (microwave background radiation), pp. 61-2 Wood, Brad, astronomer, p. 46 Wyller, Arnie, Swedish astronomer, p. 46 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Dr_Martin_Pomerantz_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Dr_Martin_Pomerantz_2.mp3 Dr. Martin Pomerantz, a physicist who specialized in cosmic ray research, had a long and distinguished career in polar studies. As a graduate student at the University of Pennsylvania he took a challenging course in 1938 at the Bartol Research Foundation of the Franklin Institute, a course called Cosmic Rays and Nuclear Physics. At the time researchers were using balloons and ships to determine how the intensity of cosmic rays, which came into the Earth’s outer atmosphere from space, varied according to geomagnetic latitude and the location of the Earth. There were only two locations on Earth –the geomagnetic pole in Antarctica, and a second one in northern Canada – where cosmic rays were not impeded by the earth’s magnetic field. Pomerantz found the graduate course at Bartol fascinating, decided to pursue a Ph.D. in physics, and started a long career that took him both to Antarctica and the Arctic region. It was the International ...